Income development of General Practitioners in eight European countries from 1975 to 2005 - Van der Zee Jouke; Kroneman Madelon W; Groot Wim (BMC, 2009)
Abstract Background This study aims to gain insight into the international development of GP incomes over time through a comparative approach. The study is an extension of an earlier work (1975-1990, conducted in five yearly intervals). The research questions to be addressed in this paper are: 1) How can the remuneration system of GPs in a country be characterized? 2) How has the annual GP income developed over time in selected European countries? 3) What are the differences in GP incomes when differences in workload are taken into account? And 4) to what extent do remuneration systems, supply of GPs and gate-keeping contribute to the income position of GPs? Methods Data were collected for Belgium, Denmark, Germany, Finland, France, the Netherlands, Sweden and the United Kingdom. Written sources, websites and country experts were consulted. The data for the years 1995 and 2000 were collected in 2004-2005. The data for 2005 were collected in 2006-2007. Results During the period 1975-1990, the income of GPs, corrected for inflation, declined in all the countries under review. During the period 1995-2005, the situation changed significantly: The income of UK GPs rose to the very top position. Besides this, the gap between the top end (UK) and bottom end (Belgium) widened considerably. Practice costs form about 50% of total revenues, regardless of the absolute level of revenues. Analysis based on income per patient leads to a different ranking of countries compared to the ranking based on annual income. In countries with a relatively large supply of GPs, income per hour is lower. The type of remuneration appeared to have no effect on the financial position of the GPs in the countries in this study. In countries with a gate-keeping system the average GP income was systematically higher compared to countries with a direct-access system. Conclusion There are substantial differences in the income of GPs among the countries included in this study. The discrepancy between countries has increased over time. The income of British GPs showed a marked increase from 2000 to 2005, due to the introduction of a new contract between the NHS and GPs.